Análisis de los sistemas de semillas en pequeños agricultores de las comunidades de Cotopaxi y Chimborazo, 2024” - Villavicencio Rodríguez, Fausto Daniel (2024)
This research was developed around small farmers in the provinces of Cotopaxi and Chimborazo in 10 communities, these are areas where agriculture is a traditional practice of indigenous and peasant communities, has been developed since ancient times with the use of seeds that have been adapted to the environmental conditions of each region, the conservation of these plant genetic resources is relevant because they are at risk of genetic erosion by factors such as changes in consumption habits in rural and urban population, replacement of native varieties by commercial ones. The objective of the study is to analyze the seed systems of potato (Solanum tuberosum L.), maize (Zea mays L.), and melloco (Ullucus tuberosus Loz.), in the provinces of Cotopaxi and Chimborazo. For the analysis, information was collected from the study areas with the application of a survey adapted and designed under study indicators based on varietal preference and/or aptitude, seed availability, selection, access and conservation of seeds. Twenty-one seed potato ecotypes were recorded, identifying Suprema, Leona Blanca, Chola, Superchola, Chaucha, and Fripapa as the best known, 11 ecotypes of maize seed, with white maize and 7 ecotypes of melloco seed, the best known being yellow melloco, these and more ecotypes are distributed in the two provinces. The selection and storage practices vary according to the seed and province.